2019
DOI: 10.1071/en19089
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of known and unknown terpenoid organosulfates in PM10 using untargeted LC–HRMS/MS: contrasting summertime rural Germany and the North China Plain

Abstract: Environmental context. Secondary organic aerosols account for a major fraction of atmospheric particulate matter, affecting both climate and human health. Organosulfates, abundant compounds in organic aerosols, are difficult to measure because of the lack of authentic standards. Here we quantify terpene-derived organosulfates in atmospheric particulate matter at a rural site in Germany and at the North China Plain using a combined target/non-target high-resolution mass spectrometry approach.Abstract. Organosul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 70 publications
(131 reference statements)
1
40
0
Order By: Relevance
“…A major fraction organic species detected in ESI− are attributed to CHO− and CHON−, accounting for 30−42% and 39−55% in terms of peak abundance, respectively, and comprising 39-45% and 23-33% in terms of peak numbers, respectively. This is consistent with previous studies on Chinese urban OA by Wang et al (2017 and and Brüggemann et al (2019). Comparing the organic compounds detected in ESI− for the three cities, 139 formulas were observed in all cities as common formulas ( Fig.…”
Section: General Characteristicssupporting
confidence: 92%
See 3 more Smart Citations
“…A major fraction organic species detected in ESI− are attributed to CHO− and CHON−, accounting for 30−42% and 39−55% in terms of peak abundance, respectively, and comprising 39-45% and 23-33% in terms of peak numbers, respectively. This is consistent with previous studies on Chinese urban OA by Wang et al (2017 and and Brüggemann et al (2019). Comparing the organic compounds detected in ESI− for the three cities, 139 formulas were observed in all cities as common formulas ( Fig.…”
Section: General Characteristicssupporting
confidence: 92%
“…Our recent Orbitrap MS study (Wang et al, 2018) showed that wintertime OA in PM2.5 collected in Beijing, China and Mainz, Germany were very different in terms of chemical composition. In contrast, for summertime OA from Germany and China, Brüggemann et al (2019) found similar compounds and concentrations of terpenoid organosulfates in PM10, demonstrating that biogenic emission can significantly affect OA composition at both locations. Ning et al (2019) analyzed the OA collected https://doi.org/10.5194/acp-2019-908 Preprint.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In the literature, there are few studies related to non-target analysis in ambient air using liquid chromatographic techniques coupled to high-resolution mass spectrometry [ 34 , 35 , 36 , 37 , 38 ], but in some cases, only MS 2 fragmentation data were employed. The other published studies in the literature employed gas chromatography [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%